Sentencing Inconsistencies in Terrorism Cases in Indonesia: Issues of Enforcement and Fairness - Fenton, Adam J. (Perspectives on terrorism, 2024)
This article examines the mechanisms for prosecuting and sentencing prisoners convicted of terrorism offences in Indonesia, using case studies to illustrate inconsistencies and discrepancies in legal processes. It begins by briefly outlining the legal processes for criminal sentencing and the realities of sentencing practices in the Indonesian context. Data on arrests, sentencing, and executions of terrorism suspects in the period 2003-2015 are analysed, revealing that over ninety percent of Indonesia’s convicted terrorists were sentenced to ten years or less in prison, with only a small percentage receiving longer sentences or the death penalty. The article argues that while sentencing of terrorists is overwhelmingly lenient, the lack of sentencing guidelines, an emphasis on judicial discretion, absence of the doctrine of precedent, lack of access to previous decisions of lower courts, and opacity of sentencing outcomes in reported decisions all contribute to inconsistency in judicial reasoning and sentencing, ultimately denying natural justice to individuals who come before the courts. The second part of the article examines individual cases which illustrate particular aspects of terrorism sentencing, such as excessive lenience or harshness, inaccurate or opaque indictments/judgements, and the treatment of women and child terrorism offenders.